A prospective observational study of prevalence and outcomes of patients with Gold Standard Framework criteria in a tertiary regional Australian Hospital. Issue 1 (21st September 2015) - Milnes, Sharyn; Orford, Neil R; Berkeley, Laura; Lambert, Nigel; Simpson, Nicholas; Elderkin, Tania; Corke, Charlie; Bailey, Michael
Abstract : Objectives: Report the use of an objective tool, UK Gold Standards Framework (GSF) criteria, to describe the prevalence, recognition and outcomes of patients with palliative care needs in an Australian acute health setting. The rationale for this is to enable hospital doctors to identify patients who should have a patient-centred discussion about goals of care in hospital. Design: Prospective, observational, cohort study. Participants: Adult in-patients during two separate 24 h periods. Main outcome measures: Prevalence of in-patients with GSF criteria, documentation of treatment limitations, hospital and 1 year survival, admission and discharge destination and multivariate regression analysis of factors associated with the presence of hospital treatment limitations and 1 year survival. Results: Of 626 in-patients reviewed, 171 (27.3%) had at least one GSF criterion, with documentation of a treatment limitation discussion in 60 (30.5%) of those patients who had GSF criteria. Hospital mortality was 9.9%, 1 year mortality 50.3% and 3-year mortality 70.2% in patients with GSF criteria. One-year mortality was highest in patients with GSF cancer (73%), renal failure (67%) and heart failure (60%) criteria. Multivariate analysis revealed age, hospital length of stay and presence of the GSF chronic obstructive pulmonary disease criteria were independently associated with the likelihood of an in-hospital treatment limitation. Non-survivors at 3 years were more likely to have a GSF cancer (25% vs 6%, p=0.004), neurological (10% vs 3%, p=0.04), or frailty (45% vs 3%, p=0.04) criteria. After multivariate logistic regression GSF cancer criteria, renal failure criteria and the presence of two or more GSF clinical criteria were independently associated with increased risk of death at 3 years. Patients returning home to live reduced from 69% (preadmission) to 27% after discharge. Conclusions: The use of an objective clinical tool identifies a high prevalence of patients with palliative care needs in the acute tertiary Australian hospital setting, with a high 1 year mortality and poor return to independence in this population. The low rate of documentation of discussions about treatment limitations in this population suggests palliative care needs are not recognised and discussed in the majority of patients. Trial registration number: 11/121.